Effect of Nitrogen Fertilizer Application on Corn Residue Decomposition in Iowa. (1st September 2017) - Al‐Kaisi, Mahdi M.; Kwaw‐Mensah, David; Ci, En
Abstract : Core Ideas: Application of 32% urea ammonium nitrate after harvest has no effect on residue decomposition. Three months after N addition, 54 to 69% of residue remained with no N rate differences. The remaining amount of residue after 12 mo was 35 to 49% across all N treatments. Incubation study shows soil temperature as a major factor in residue decomposition. Nitrogen addition suppressed CO2 –C evolution during residue incubation. Corn ( Zea mays L.) residue is one of the sources of soil organic carbon (SOC) in row cropping systems in the Midwest. Farmers in Iowa apply liquid N to corn residue after harvest, assuming it will increase corn residue decomposition. The objective of this study was to investigate the effectiveness of N application for increasing corn residue decomposition. The study included two fields with three N rates (0, 34, or 67 kg N ha −1 ) of liquid 32% urea ammonium nitrate (UAN) applied after harvest, and two laboratory incubation experiments with three temperatures (0, 25, and 35°C) in 2012 and 2013. The experiment design was a randomized complete block in four replications in a no‐tillage system (NT). The average mass of residue organic carbon (OC) after harvest was in the range of 1.6 to 1.7 Mg ha −1 . Residue OC in the field declined sharply in both years, particularly during the first 3 mo, with no significant difference between N treatments. The only difference in field residue decomposition occurred after 6 mo ( P = 0.0241) at the Olson location in 2012, where a greater (>21%) amount of remaining OC was associated with 0 kg N ha −1 than with other N treatments. The incubation study showed an increasing rate of residue decomposition with increasing soil temperature with no N application effects on residue decomposition. These findings show that air and soil temperatures are the driving force for residue decomposition, especially at 25°C, rather than with N addition.